El Carnaval de Oruro y su Incidencia en el Proceso Artístico Pedagógico para la Creación del Montaje Interdisciplinar el Conjuro del Chiru Chiru “Un Camino de Sensación, Creación y Vida” (2017)
This degree work is the culmination of the formative research process of the master artist in training of the Bachelor's Degree in Artistic Education with emphasis on Dance and Theater - Faculty of Education of the Antonio Nariño University. Their developments, contributions, scope, questions and projections contribute to the growth of the Performing Arts Didactic Research Group and are part of the Line that bears the same name.